(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2021)
The openness of border areas under the influence of the integration process taking place in the world community as a result of socio-economic transformations in the countries facilitates cooperation in the development of cross-border tourism between neighboring countries. There are great opportunities for the joint development of cross-border tourism between the Almaty region of Kazakhstan and the IssykKul region of the Kyrgyz Republic. This paper aims to investigate the evaluation of the potential of crossborder tourism cooperation between the southern part of Almaty and the northern part of the Issyk-Kul region. The methodological basis of the research presented in this article is comprised of information from periodicals, reference sources and data from the Federal State Statistics Service of relevant countries. The research was carried out using the comparative geographical, cartographic, statistical methods. The results show that there are a lot of tourist facilities near the border between the two regions, roads between the two regions are highly developed, strategic projects for joint tourism development are being implemented between the two regions, both regions have great potential for tourism development, a comparatively large number of tourists flow to these two regions every year, and these two regions have the advantage of geographical location to receive millions of Chinese tourists. From the above results, we easily assess that there is great potential for cooperation in cross-border tourism between the two regions.